Root Dentin Transparency: A Reliable Method of Age Estimation in Nepalese Population - Adhikari, Bhoj Raj; Shakya, Mamata; Upadhyaya, Chandan; Mahanta, Swagat Kumar; Chaurasia, Nitesh; Poudel, Pratibha; Singh, Pankaj Kumar; Srii, Ritesh; Lamichhane, Simant (Journal of Nobel Medical College, 2023)
Background: Root dentin transparency, one of the age changes in dentin, is considered to be a stable parameter not affected by environmental and pathological factors. The effect of age changes in the transparency of root dentin in Nepalese population have not been established so far. In the present study, we aimed to determine the age of an individual using the root dentin transparency in the Nepalese subjects and attempt to derive the formula to estimate the age applicable to the Nepalese population. Materials and Methods: A cross sectional analytical study was conducted to measure the length of root dentin transparency in the tooth of patients of known age. Correlation of the age and the length of transparent root dentin was determined. A linear regression analysis was carried out to derive a formula applicable to the Nepalese population. Results: The length of transparent root dentin increased linearly with the age of an individual. The newly derived formula was used to calculate the estimated age from the length of transparent root dentin. The difference between the actual age and the calculated age was within 6 years in 63.2% of the sample. Conclusion: A simple and relatively inexpensive method for calculating age by measuring RDT is described.